2018
DOI: 10.1101/gr.237073.118
|View full text |Cite
|
Sign up to set email alerts
|

High-salt–recovered sequences are associated with the active chromosomal compartment and with large ribonucleoprotein complexes including nuclear bodies

Abstract: The mammalian cell nucleus contains numerous discrete suborganelles named nuclear bodies. While recruitment of specific genomic regions into these large ribonucleoprotein (RNP) complexes critically contributes to higher-order functional chromatin organization, such regions remain ill-defined. We have developed the high-salt–recovered sequences-sequencing (HRS-seq) method, a straightforward genome-wide approach whereby we isolated and sequenced genomic regions associated with large high-salt insoluble RNP compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…Indeed, our recent work in mouse embryonic stem cells showed that HRS include sequences associated with nuclear bodies (like the Cajal bodies, the HLBs, the speckles and paraspeckles). Moreover, transcriptional condensates formed around super-enhancers are also retained in our assay [52]. In full agreement with the first prediction, we found that two classes of genes can be defined according to the criterion of their association (or lack thereof) with large high-salt insoluble RNP complexes [52].…”
Section: Hrs-seq: a Novel Methods To Explore Nuclear Bodies-associatedsupporting
confidence: 85%
See 3 more Smart Citations
“…Indeed, our recent work in mouse embryonic stem cells showed that HRS include sequences associated with nuclear bodies (like the Cajal bodies, the HLBs, the speckles and paraspeckles). Moreover, transcriptional condensates formed around super-enhancers are also retained in our assay [52]. In full agreement with the first prediction, we found that two classes of genes can be defined according to the criterion of their association (or lack thereof) with large high-salt insoluble RNP complexes [52].…”
Section: Hrs-seq: a Novel Methods To Explore Nuclear Bodies-associatedsupporting
confidence: 85%
“…Moreover, transcriptional condensates formed around super-enhancers are also retained in our assay [52]. In full agreement with the first prediction, we found that two classes of genes can be defined according to the criterion of their association (or lack thereof) with large high-salt insoluble RNP complexes [52]. Our work showed that HRS-located genes are highly expressed and associated with the active chromosomal compartment and active super-enhancers in a cell-type specific manner, while genes that do not lie in HRS are moderately or weakly expressed.…”
Section: Hrs-seq: a Novel Methods To Explore Nuclear Bodies-associatedmentioning
confidence: 83%
See 2 more Smart Citations
“…1h, i, Supplementary Table 2). Of note, other chromatin fractionation-based NGS methods have been previously described 41,42 , however they are not directly comparable to our technology as they adopt different conditions, enzymes and cellular models.…”
Section: Sammy-seq Allows Mapping Of Lamina Associated Heterochromatimentioning
confidence: 99%